Embodied design strategies for autism-friendly museums: a Kano-QFD-PUGH-based user needs assessment - Qian, Sijin; Mao, Keren; Yi, Xinyue (Frontiers in Psychiatry, 2025)
IntroductionIn the context of a global push for child-friendly environments, this study investigates the specific design needs of children with Autism Spectrum Disorder (ASD) in museum settings. The objective is to develop a user-centered evaluation model that can inform inclusive design strategies.MethodsWe propose an integrated methodology combining the Kano model, Quality Function Deployment (QFD), and the PUGH matrix to assess and optimize museum design for autistic children. Results reveal that designs tailored to user needs significantly improve key experience factors, such as emotional engagement, interaction, and safety.ResultsIn particular, the “Science and Technology Interactive Museum” option—featuring AR/VR interaction and spatial guidance—achieved the highest satisfaction scores in our evaluation. This design improvements lead to an approximate 23% increase in user satisfaction, significantly enhancing the overall museum experience for autistic children.DiscussionThese findings demonstrate the value of structured user-driven design approaches in enhancing cognitive and emotional engagement for autistic children in museum environments.